2015
DOI: 10.1038/onc.2014.437
|View full text |Cite
|
Sign up to set email alerts
|

TM9SF4 is a novel V-ATPase-interacting protein that modulates tumor pH alterations associated with drug resistance and invasiveness of colon cancer cells

Abstract: An inverted pH gradient across the cell membranes is a typical feature of malignant cancer cells that are characterized by extracellular acidosis and cytosol alkalization. These dysregulations are able to create a unique milieu that favors tumor progression, metastasis and chemo/immune-resistance traits of solid tumors. A key event mediating tumor cell pH alterations is an aberrant activation of ion channels and proton pumps such as (H+)-vacuolar-ATPase (V-ATPase). TM9SF4 is a poorly characterized transmembran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
58
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 74 publications
(62 citation statements)
references
References 52 publications
4
58
0
Order By: Relevance
“…TM9SF4 knockdown is associated with a significant inhibition of the invasive behavior of colon cancer cells and with increased sensitivity to the effect of chemotherapeutics. These effects were also consistent with reversing tumor pH gradient with a decrease of cytosolic pH, alkalization of intracellular vesicles and a reduction of extracellular acidity 29 , further supporting the importance of TM9SF4 as a potential target for future anticancer therapies. All in all this line of research, that started simply from the microscopic observation of the cells within other cells, has led to the discovery of a new oncoprotein involved in a key function DOI: 10.3109/14756366.2016.1156105 of malignant cells, that is the ability to feed on other cells, probably representing a very important butt for future anticancer therapies, whose discovery was achieved through a definitive nonmainstream way of doing research in medicine.…”
Section: Example 2: Cancer Cells Behave As Amoebassupporting
confidence: 60%
See 1 more Smart Citation
“…TM9SF4 knockdown is associated with a significant inhibition of the invasive behavior of colon cancer cells and with increased sensitivity to the effect of chemotherapeutics. These effects were also consistent with reversing tumor pH gradient with a decrease of cytosolic pH, alkalization of intracellular vesicles and a reduction of extracellular acidity 29 , further supporting the importance of TM9SF4 as a potential target for future anticancer therapies. All in all this line of research, that started simply from the microscopic observation of the cells within other cells, has led to the discovery of a new oncoprotein involved in a key function DOI: 10.3109/14756366.2016.1156105 of malignant cells, that is the ability to feed on other cells, probably representing a very important butt for future anticancer therapies, whose discovery was achieved through a definitive nonmainstream way of doing research in medicine.…”
Section: Example 2: Cancer Cells Behave As Amoebassupporting
confidence: 60%
“…This line of research has led to the discovery of a protein that amoebas and cancer cells share, TM9SF4 28 , that is related to their ability, to cannibalize other cells 26 . More recently, the same line of research has shown that TM9SF4 represents a novel V-ATPase-associated protein involved in V-ATPase activation 29 . V-ATPase is a proton pump highly active in malignant tumors we have shown to be a target, while not fully specific, of PPI 9,11 .…”
Section: Example 2: Cancer Cells Behave As Amoebasmentioning
confidence: 97%
“…Finally, the transmembrane protein TM9SF4 has been shown to interact with the V-ATPase and modulate activity through regulation of pump assembly. Silencing of TM9SF4 in colon cancer cells reduces in vitro invasiveness (103). Thus the roles of V-ATPases in promoting tumor cell invasion and migration may be complex, and additional studies will be required to fully elucidate these roles.…”
Section: Mechanism Of V-atpase Promotion Of Tumor Cell Invasion Anmentioning
confidence: 98%
“…In ER␣ϩ breast cancer patients, a molecular subtype which makes up ϳ70% of all breast cancers, DMXL2 is upregulated in the 40% of these patients who continue to progress on therapy (40). Targeting the transmembrane protein TM9SF4, another positive enhancer of V-ATPase activity, increases drug sensitivity (103).…”
Section: Function Of V-atpases In Cancermentioning
confidence: 99%
“…V‐ATPase function has also been demonstrated to be influenced by the transmembrane protein TM9SF4 and ceramide synthase (LASS2/TMSG1) although the molecular basis for these functional links remain only partially understood 25, 26…”
Section: V‐atpase Structure and Function In Normal Physiologymentioning
confidence: 99%